Dysphagia Due to Inclusion Body Myositis: Case Presentation and Review of the Literature. (September 2014) - Ko, Ellen H.; Rubin, Adam D.
Objective: This report aimed to present a case of inclusion body myositis presenting with dysphagia and to review the literature. Methods: Case report and literature review. Results: Inclusion body myositis is a chronic progressive acquired myopathy, uniquely distinguished by its selective muscle involvement, normal or moderately elevated muscle enzyme concentrations, and a progressive corticosteroid-resistant course. Compared to other inflammatory myopathies, the esophagus is the most commonly involved organ. Specifically, upper esophageal sphincter dysfunction often occurs. Dysphagia may be the only symptom at the time of presentation. Conclusion: Unlike other inflammatory myopathies, dysphagia in inclusion body myositis is steroid resistant. Management can be difficult. The otolaryngologist must consider underlying neuromuscular processes when evaluating the patient presenting with oropharyngeal dysphagia.